Retrospective evaluation of patients diagnosed solid pseudopapillary neoplasms of the pancreas. - Ercelep, Ozlem; Ozdemir, Nuriye; Turan, Nedim; Topcu, Turkan Ozturk; Uysal, Mukremin; Tanriverdi, Ozgur; Demirci, Umut; Taskoylu, Burcu Yapar; Urakcı, Zuhat; Duran, Ayse Ocak; Aksoy, Asude; Menekse, Serkan; et al. (My University, 2019)
Solid pseudopapillary neoplasm (SPN) is a rare, low-grade neoplasm with excellent prognosis. In this study, we evaluated clinicopathological characteristics of patients diagnosed with SPN retrospectively.

This is a retrospective study intended to characterize patients with the diagnosis of SPN between 2005 and 2015. Clinicopathological features, recurrence rate, and overall survival of 28 patients were recorded. Malignant SPN criteria were defined as the presence of distant metastasis (developed at diagnosis or during follow up) or lymph node involvement.

The mean age at diagnosis was 42 (range: 17-41). Among patients, 82% (n = 23) were female and 17.9% (n = 5) were male. The mean size of tumor was 5.81 cm (range: 2-15). The mean follow up period was 55.6 months, 1-year survival was 96.5% and 5-year survival rate was 88%. A total of 25 patients were alive at the end of follow-up period and 3 of the patients became exitus due to disease. Two patients had a metastatic presentation in livers at the diagnosis and metastasis developed in 3 patients during follow-up (liver of 1 patient, peritoneum in 1 patient and liver and peritoneum in 1 patient). The reason of admission was headache in 68% patients. The type of operation was frequently subtotal pancreatectomy (n = 11, 39.3%) and distal pancreatectomy (n = 10, 35.7%). Tumors were located frequently in body and tail regions (n = 18, 64.3%) and the number of patients with malignant criteria was 6 (21.4%). Although the mean age of malignant patients was significantly higher than benign patients (P = 0.046), there was no significant difference between 2 groups in terms of gender, tumor size, capsule invasion, perineural invasion, vascular invasion, and margin status.

SPN is a rarely seen tumor with low malignity potential. Surgical resection provides long-term survival rate even in local invasion or metastasis conditions.
Keywords: Pancreatic Tumor; Solid pseudopapillary Neoplasm; Survival; Treatment